DAMPAK IMPLEMENTASI MOBILE JKN TERHADAP KECEPATAN AKSES INFORMASI DAN KLAIM PESERTA BPJS KESEHATAN DI RSIA X TAHUN 2025 - Fitriani Astika; Sy.Effi Daniati; Wen Trisna Via (Journal of Hospital Administration and Management (JHAM), 2026)
The implementation of digital transformation in healthcare services has encouraged BPJS Kesehatan to introduce the Mobile JKN application as an effort to improve service efficiency and accessibility for National Health Insurance (JKN) participants. This study aimed to analyze the impact of Mobile JKN implementation on the speed of information access and claim services for BPJS Kesehatan participants at RSIA X in 2025. This research used a qualitative method with a case study approach. Data were collected through observations, in-depth interviews, and documentation involving three active JKN participants who used the Mobile JKN application and two BPJS service officers. Data analysis was conducted using content analysis techniques. The results showed that the implementation of Mobile JKN accelerated access to participant information, online queue services, service schedules, and referral status digitally. The application also improved administrative service efficiency through faster participant data verification and reduced queues at administrative counters. In addition, the use of Mobile JKN accelerated the claim service process because participant data had been integrated with the BPJS Kesehatan system. However, several obstacles were still identified, including internet network disruptions, system errors, and low digital literacy among some participants. Overall, the implementation of Mobile JKN had a positive impact on improving the quality of digital-based BPJS Kesehatan services.